Construction of all-polyimide fiber based paper with high breakdown strength and stable properties for advanced insulation - Xiuzhi Qin; Xiuting Li; Jie Dong; Qingsong Xu; Xin Zhao; Qinghua Zhang (Polymer Testing)
All-polyimide (PI) fiber based composite paper integrate the excellent insulation properties and heat resistance with lightweight and highly designable characteristics, making them ideal for insulation in ultra-high voltage transmission and new power systems. The key to fabricate all PI fiber based composite paper lies in the interface combination inside the composites, which strongly depended on the adhesive components. In this study, PI structures with trifluoromethyl and amide units were synthesized and its precipitated fibers with microfibrillated morphologies were prepared, which could fully utilize the hydrogen bonding and physical bunding to combine with commercial PI chopped fibers, thus enhancing the comprehensive performance of all PI fiber based composite paper. By optimizing the preparation process, the mechanical strength of the obtained PI paper could reach 11 MPa with a breakdown strength of up to 41.7 kV/mm, meeting the requirements of H-level or above insulation paper. Additionally, as-prepared PI paper demonstrated stable dielectric properties and integrated structures under complex working circumstances, such as wide temperature ranges, hydrothermal environments, acidic and oil immersion conditions, providing strong assurance for the safe and stable operation of ultra-high voltage transmission power systems in the future.